Microplastic Abundance in The Waters of The Middle Section of The Citarum River, Karawang, West Java - Hermana, Indra Setiadi; Hariyadi, Sigit; Taryono, Taryono; Hidayat (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
Microplastics in the Central Citarum River, Karawang, West Java, originate from anthropogenic activities of people living around the watershed, which is an industrial, agricultural, and densely populated residential area. Microplastics are degraded plastics < 5 mm in size. This study aims to determine the abundance and size of microplastics in the Middle Citarum River, through observation with a microscope. Sampling was conducted at three locations with three observations: February, March, and April 2022. The types of microplastics found were pellets, films, fibers, and fragments. Microplastic particle size < 0.3 mm was the most common size found. The abundance of microplastics in the water of the Middle section of the Citarum River is different at each sampling location. The total number of microplastic particles in all research locations was 4,413 particles. The highest abundance of microplastics in all sampling locations was in densely populated residential areas at 239.7 ± 326.7 particles/m3 , followed by agricultural areas with an abundance of 72.5 ± 63.8 particles/m3 , then the lowest abundance was in industrial areas at 55.6 ± 57.8 particles/m3. The average abundance of microplastics in the middle Citarum River water was 122.6 ± 209.7 particles/m3. Statistical analysis using Kruskall Wallis with a df value of 2 > 0.05 showed no significant difference in microplastic abundance at each research location. All stations had the same potential for microplastic pollution. This study shows that high anthropogenic activities lead to high microplastic pollution in water. Therefore, proper mitigation and management of waste and plastic waste are needed.